Religion and politics in the modern world - Kumar, Vikramendra (New Delhi Global Vision Publishing House, 2022)
The book Religion and Politics in the Modern World offers styudents with an accessible yet in-depth introduction of the most important debates, issues and techniques in the field of religion and politics.
Keywords: Modernity and Hinduism; religion and politics; Religious freedom and secularism